Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) dengan Metode HAZOP di Unit Gardu Induk 150 kV Jeranjang - Hati, Mutiara Indah Permata; Adnyani, Ida Ayu Sri; Putra, I Ketut Perdana (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Occupational safety and health (OHS) in the industrial environment, especially in the 150 kV Jeranjang Substation Unit is very important, which has the potential to face various risks. This study uses the Hazard and Operability Study (HAZOP) method to identify and analyze existing risks. Through observation and interviews, data was collected and analyzed, resulting in the identification of 11 potential hazards from 11 equipment with varying levels of risk. From the results of the analysis, it was found that 82% of the risks were in the high category, 9% were moderate and 9% were low. This study shows that the application of the HAZOP method is effective in identifying OHS risks in the unit. Recommendations provided include the need for regular training for employees, the implementation of stricter work procedures and periodic evaluation of the existing OHS system. With these steps, it is expected to improve occupational safety and reduce the possibility of work accidents in the 150 kV Jeranjang Substation environment.